Eigenvalue problems for Schrödinger-Bopp-Podolsky systems - Hernandez, Lorena Soriano (2021)
This work is framed in the study of a class of Schrödinger-Bopp-Podolsky systems. As a novelty, we apply topological methods to find solutions of equations that involve the bi-Laplacian operator as well as such solutions are defined in subsets of R^N where N 3.